Teachers' motivational profiles and their longitudinal associations with teaching quality. (December 2021) - Thommen, Désirée; Sieber, Vanda; Grob, Urs; Praetorius, Anna-Katharina
Abstract: This study used an integrated theoretical approach to investigate teacher motivation and its influence on teaching quality. Drawing on Expectancy-Value-Theory and Achievement-Goal-Theory, a person-centered approach was used to investigate how multiple characteristics (i.e., self-efficacy, enthusiasm, and goal orientation) combined to form teachers' motivational profiles. The profiles were then analyzed to see if there was a link to teaching quality. Latent profile analysis for 156 secondary-level mathematics teachers identified three motivational profiles which differed only in their performance goals: low performance goal-oriented (49%), high performance goal-oriented (38%), and high performance-avoidance goal-oriented (13%). Multilevel path analysis showed that motivational profile membership was not significantly related to student-rated teaching quality when baseline teaching quality was controlled ( N  = 1497 available on both measurement points). The findings revealed that the link between teacher motivation and teaching quality was less clear than expected. Possible reasons for the results are discussed. Highlights: Latent profile analysis was used for identifying teachers' motivational profiles. Teachers' motivational profiles mainly differed regarding their performance goals. An integrated theoretical approach on teacher motivation indicated no added value. Profile membership did not predict change in teaching quality.